(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Aicardi Goutieres Syndrome is an early-onset leukoencephalopathy with a presumed immune pathogenesis caused by inherited defects in nucleic acid metabolism. It is an inflammatory disorder resulting from mutation of multiple genes. Majority of the affected individuals experience physical as well as intellectual disability. Here we discuss a case of A 2-year old girl of consanguineous marriage diagnosed as Aicardi Goutieres Syndrome who was presented with the sudden loss of motor and cognitive skills after an acute febrile illness. This syndrome was diagnosed by clinical exome sequencing and RNAEH 2A mutant gene identification. J Bangladesh Coll Phys Surg 2022; 40: 132-135